Incidence of Hypertensive Disorders of Pregnancy in Women with COVID-19 - Chornock, Rebecca; Iqbal, Sara N.; Wang, Tiffany; Kodama, Samantha; Kawakita, Tetsuya; Fries, Melissa (American Journal of Perinatology, 2021)
Objective The study aimed to examine the incidence of hypertensive disorders of pregnancy in women diagnosed with SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2, also known as COVID-19).Study Design This was a retrospective cohort study of all women who delivered at MedStar Washington Hospital Center in Washington, DC from April 8, 2020 to July 31, 2020. Starting April 8, 2020, universal testing for COVID-19 infection was initiated for all women admitted to labor and delivery. Women who declined universal testing were excluded. Hypertensive disorders of pregnancy were diagnosed based on American College of Obstetricians and Gynecologists Task Force definitions.1 Maternal demographics, clinical characteristics, and labor and delivery outcomes were examined. Neonatal outcomes were also collected. Laboratory values from admission were evaluated. Our primary outcome was the incidence of hypertensive disorders of pregnancy among women who tested positive for COVID-19. The incidence of hypertensive disorders of pregnancy was compared between women who tested positive for COVID-19 and women who tested negative.Results Of the 1,008 women included in the analysis, 73 (7.2%) women tested positive for COVID-19, of which 12 (16.4%) were symptomatic at the time of admission. The incidence of hypertensive disorders of pregnancy was 34.2% among women who tested positive for COVID-19 and 22.9% women who tested negative for COVID-19 (p = 0.03). After adjusting for race, antenatal aspirin use, chronic hypertension, and body mass index >30, the risk of developing any hypertensive disorder of pregnancy was not statistically significant (odds ratio: 1.58 [0.91–2.76]).Conclusion After adjusting for potential confounders, the risk of developing a hypertensive disorder of pregnancy in women who tested positive for COVID-19 compared with women who tested negative for COVID-19 was not significantly different.Key Points
Keywords: hypertension; COVID-19; coronavirus; preeclampsia; pregnancy